2020
DOI: 10.1111/xen.12581
|View full text |Cite
|
Sign up to set email alerts
|

Co‐transplantation of human adipose‐derived mesenchymal stem cells with neonatal porcine islets within a prevascularized subcutaneous space augments the xenograft function

Abstract: Background Cell transplantation has been widely recognized as a curative treatment strategy for variety of diseases including type I diabetes (T1D). Broader patient inclusion for this therapeutic option is restricted by a limited supply of healthy human islet donors and significant loss of islets immediately postintrahepatic transplant due to immune activation. Neonatal porcine islets (NPIs) are a potential ubiquitous β‐cell source for treating T1D. Mesenchymal stem cells (MSCs) have the inherent capacity to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…Regarding immunomodulation, ADMSCs support immunotolerance in the transplant site by hindering the infiltration of CD4+ and CD8+ T cells [95] and macrophages [94], as well as by promoting the production and infiltration of Tregs [96]. A recent study revealed that xenogeneic co-transplantation of human ADMSCs with neonatal porcine islets led to earlier achievement normoglycemia in diabetic mice compared with transplantation of porcine islets only [97]. These functions of ADMSCs are characterized as supportive effects for promoting the engraftment of transplanted islets.…”
Section: Admscsmentioning
confidence: 99%
“…Regarding immunomodulation, ADMSCs support immunotolerance in the transplant site by hindering the infiltration of CD4+ and CD8+ T cells [95] and macrophages [94], as well as by promoting the production and infiltration of Tregs [96]. A recent study revealed that xenogeneic co-transplantation of human ADMSCs with neonatal porcine islets led to earlier achievement normoglycemia in diabetic mice compared with transplantation of porcine islets only [97]. These functions of ADMSCs are characterized as supportive effects for promoting the engraftment of transplanted islets.…”
Section: Admscsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are widely used to be co-transplanted with islets. [35][36][37][38][39] When co-transplanted with islets in recipients, MSCs can promote angiogenesis in situ to prevent hypoxia and to attenuate immune rejection. MSCs can suppress various immune cells such as NK cells, macrophages, neutrophils, and T cells.…”
Section: Design Of the Hypothetical Hydrogel Modelmentioning
confidence: 99%
“…It has shown that dendritic cell (DC)‐based cell therapy has a potential to promote transplantation tolerance and could help to reduce/replace immunosuppressive treatments 8 . Madelon et al generated tolerogenic DCs by differentiating bone marrow (BM) cells in the presence of granulocyte‐macrophage colony‐stimulating factor and interleukin 10 (IL‐10 DC) 9 . IL‐10 DCs produced high amounts of IL‐10 and low amounts of pro‐inflammatory cytokines and induced weak T‐cell proliferation.…”
Section: Advances In the Management Of Rejectionmentioning
confidence: 99%